169k views
1 vote
8. [15 + (5 - 2)^2] ÷ 6 =

9. 4^3 + [7 - 2 ( 3 1/4)] - 9.2 =



8. [15 + (5 - 2)^2] ÷ 6 = 9. 4^3 + [7 - 2 ( 3 1/4)] - 9.2 = ​-example-1
User Camelid
by
5.5k points

2 Answers

2 votes
8 is 4
9 is 55.3

8 because
[15+ 3^2] / 6
15+9/6= 24/6
24/6 =4
and 9 because
3 1/4 x 2 = 6 1/2 and 7- 6 1/2= 1/2
4^3 + 1/2 - 9.2 = 64 + 1/2 - 9.2 = 64.5 -9.2= 55.3
User Paulkmoore
by
4.8k points
6 votes

Answer:

8. 24

9.55.3

Explanation:

User Adam Staszak
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.